EFFECT OF REPEATED CROPS ON SOIL AGROPHYSICAL PROPERTIES IN SHORT-ROW VEGETABLE-CEREAL, VEGETABLE-COTTON ROTATION SYSTEMS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
In article, results of researches had been adduced and analyses as the main sowing of the cotton and grain in the field of past crops, on the gray soils of Andijan region, sowing of soy, mash, corn and their effect on the agrophysical qualities of the soil.